Ash and sulfur dioxide in the 2008 eruptions of Okmok and Kasatochi: Insights from high spectral resolution satellite measurements - Prata, A. J.; Gangale, G.; Clarisse, L.; Karagulian, F. (Journal of Geophysical Research Atmospheres, 2010)
Ash particles and sulfur dioxide gas are two significant components of volcanic clouds that are important because of their effects on the atmosphere. Several different satellite instruments are capable of delivering quantitative measurements of ash and SO2, but few can provide simultaneous assessments. High‐spectral resolution (ν/Δν ∼ 1200) infrared satellite data from the Atmospheric Infrared Sounder (AIRS) are utilized to detect volcanic ash within the 8–12 μm window region, and at the same time exploit the 4.0 μm and 7.3 μm bands of SO2 to detect SO2 at two different heights. The purpose is to study the interaction between gas and particles in dispersing volcanic clouds, and investigate the circumstances when the gas‐rich and ash‐rich parts of the plume are collocated and when they separate. Simultaneous retrievals of ash and SO2 in the eruption clouds from Okmok and Kasatochi suggest that the two components were transported together for at least the first 3 days after the initial injection. Later (several days) transport is difficult to infer because of the lack of sensitivity of the ash algorithm to thin, dispersing ash clouds. For Kasatochi and Okmok, AIRS measured maximum masses of approximately 1.21 ± 0.01 Tg and 0.29 ± 0.01 Tg of SO2, and 0.31 ± 0.03 Tg and 0.07 ± 0.03 Tg of fine ash (1 μm < radii < 10 μm), respectively. The retrieval schemes described here are capable of detecting the distribution of SO2 simultaneously with estimates of ash concentrations from the same satellite instrument and represent an important improvement for observations of multispecies dispersing volcanic clouds. Analyses of other volcanic eruptions show that SO2 and ash do not always travel together. Consequently, it is concluded that for dispersing volcanic clouds it is vital to be able to detect both SO2‐rich and ash‐rich clouds simultaneously in order to diagnose their effect on the atmosphere and the aviation hazard.